GUIDELINES FOR ENHANCING KNOWLEDGE MANAGEMENT CAPABILITIES OF VOCATIONAL COLLEGES AND TECHNOLOGY IN GUANGXI PEOPLE'S REPUBLIC OF CHINA - Enhai, Shurn; Suteeniran, Niran; Suwanjarat, Tashakorn; Dechome, Pachara; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2023)
The purposes of this research are to 1) study the enhancement of knowledge management capabilities of vocational colleges. 2) evaluate the characteristics of enhancement of knowledge management capabilities of vocational colleges. 3) study the guidelines for enhancing the knowledge management capabilities of vocational colleges. Knowledge management of vocational colleges and technology in Guangxi Province People's Republic of China in 7 areas, consisting of 1) knowledge identification, 2) knowledge creation and acquisition, 3) knowledge organization, 4) knowledge processing and screening, 5) access to knowledge. Know 6) knowledge exchange aspect 7) learning aspect The research population includes vocational and technological colleges in Guangxi Province. People's Republic of China The sample group used in this study included administrators and regular teachers. Vocational Education and Technology College in Guangxi Province People's Republic of China By purposive random sampling, a total of 300 people were recruited. The group of interviewees included the president or vice-president, administrators, and permanent professors. Vocational Education and Technology College in Guangxi Province, totaling 30 people. The research results found that Guidelines for upgrading the knowledge management capabilities of vocational and technological colleges in Guangxi Province People's Republic of China Personnel are encouraged to learn by studying various documents and knowledge and applying them to work with an open mind to accept new knowledge always. Supporting the use of knowledge gained from training. or from seminars applied in work practice Support the use of knowledge to create new work. Executives have established a knowledge structure to prepare for collecting knowledge systematically. There are public relations sources for accessing knowledge to personnel. Providing opportunities to develop the potential of personnel to express their knowledge and abilities creatively to the organization